PERAN DOMINAN MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK SISWA PUTRI DALAM MENGIKUTI KEGIATAN EKSTRAKURIKULER FUTSAL (STUDI PADA SMA DR. SOETOMO SURABAYA) - YULIASARI, ADE (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Basically, physical education is an education through physical activities that created as media to achieve individual development holistically. Through physical education student channeled to physical education including sports skill. To optimize student’s existence in studying and skill, school held an extra hour outside or so called extracurricular activity. At Senior High School Dr. Soetomo Surabaya, the existing extracurricular are, achievement sports (basketball, volleyball, futsal, football, and pencak silat). Indeed, extracurricular that have the larger member is futsal since its very popular and it can be done without wide field, beside  Senior High School Dr. Soetomo Surabaya have complete infrastructure for futsal.  Female team of Senior High School Dr. Soetomo Surabaya that amounted of 11 student also have school almamater to following championship that held by universities or institutions on Surabaya or around. Research result show that the rate of intrinsic motivation on student that following extracurricular at Senior High School Dr. Soetomo Surabaya is 35.2 right on the score span 35.2-39.5 which stated that the rate of intrinsic motivation of futsal extracurricular member at Senior High School Dr. Soetomo Surabaya belong to high category. The rate if extrinsic motivation of futsal extracurricular member at Senior High School Dr. Soetomo Surabaya is 26.18 right on the score span 0-28 which stated that the rate of extrinsic motivation of futsal extracurricular member at Senior High School  Dr. Soetomo Surabaya belong to low category.      The most dominant category belong to intrinsic motivation with the percentage of intrinsic motivation is 18.8% belong to very high criterion, 36.6% belong to medium criterion, 9.09% on low category and 0% belong to very low category. Compared to extrinsic motivation that as big a 0% that belong to very high category, 0% to very high category, 0% on high category, 0% medium category, 9.09% low category and 81.81% belong to very high category. From those percentage data above it can be conclude that the most dominant role is intrinsic motivation.   Keywords: motivation, student, futsal extracurricular.